The Meaning of The Principle of Interest (Insurable Interest) in The Insurance Agreement for Legal Purposes - Zahra Mahrunisa (Magister of Law, Faculty of Law, University of Mataram, 2022)
The juridical problem in this study is that there has been no explanation of the basic meaning of interest in Law Number 14 of 2014 on Insurance (vacuum of norms), so there is no standardization of the basic meaning of interests and their characteristics. This research is juridical-normative, using legal theory, contract theory, and insurance theory, as well as using statute approach and conceptual approach. According to interest theory, the object of insurance is attached to subjective rights that are intangible. The interest is absolute, meaning it must be on every insurance object and follow wherever the insurance thing is located. The interest must already be on the insurance object at the time the insurance is held or at least at the time of the event that incurs a loss (evenemen). For the insured who have insurance, the interest is attached to the insurance object. In the context of insurance agreements, achieving interests based on fairness and benefit can not only be based on the insurance benefit but rather the benefit of the opportunity for the party that should be insured for equality.